(untitled) (Pakistan Journal of Science, 2022)
Iron doped Titanium oxide (Fe/TiO2) nanoparticles with size about 9-16 nm was synthesized by sol-gel assay based on various solvents followed by calcination for 3 hours at 700oC. The properties of the doped materials were compared in various solvents in sense of antibacterial and antioxidant behavior. Antibacterial and antioxidant potential of all synthesized nanoparticles were studiedviadisc diffusion method and free radical scavenging potential of stable 1,1- Diphenyl-2-picryl hydrazyl respectively. Result of antibacterial activity was found in the range of 7.5-10 mg/disc which shows that effect of various solvents play an important role on the antibacterial activities of Fe-doped TiO2 nanoparticles. The characterization of all synthesized nanoparticles was performed by various characterization techniques such as Thermo gravimeteric analysis (TGA), Fourier transform infra-red (FT-IR), Scanning electron microscope (SEM), Dynamic light scattering (DLS), X-ray diffraction (XRD), Photoluminescence (PL) analysis and UV-Vis spectrometer. The Fe/TiO2 nanoparticles also showed significant antioxidant activity (20-27%).